Treatment Efficacy of Oral and Intravenous Iron Delivery Routes for Anemic Pregnant Women - Amina Bukhari, Sughra Abbasi, Samina Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Although it particularly is prevalent in less-developed countries, anemia in pregnancy remains a significant problem in the developed world. It is one of the major health issues during pregnancy. The principle cause of anemia is iron deficiency, which is dependent on the patient’s dietary status. Treatment of iron deficiency anemia is critically essential during pregnancy to prevent bad maternal and neonatal outcomes Objective: The study aimed to compare the oral and intravenous iron delivery routes in anemic pregnant women. Study design: It is an experimental study. The 120 patients who visited the gynecology department of the hospital for the duration of one year from June 2021 to May 2022 were selected. Material and Methods: The data was taken from 120 patients that were admitted in Department of Obstetrics and Gynecology of Sindh Government Hospital Landis, The duration of study was one year. All the patients were aware of the study, as written consent was taken from them. The oral iron intake was given to 58 women and to the other 62 women the intravenous injections of iron was administrated during their pregnancy. All the participants completed their follow-up sessions throughout the year. The blood samples and the other data related to pregnancy was collected from each patient. Results: The back-count of tablets was carried out and it was observed that almost 89% women took their iron supplements daily. There were only 5% patients that took 50% of their iron tablets. The average dose that was given to women was 600mg in case of elemental intravenous iron. The average level of iron and ferritin are observed to be higher in the group administrated with intravenous injection as compared to the other group. The chances of hemoglobin rise were more in case of intravenously administered patients. Conclusion: The study was carried out to compare the oral and intravenous iron delivery routes in anemic pregnant women. It was found that intravenous delivery route of iron in form of iron sucrose is safe and an effective method for the iron therapy in anemic pregnant women, as it restores the hemoglobin stores efficiently as compared to other group. However, it is costly as it need hospitalization. As an alternative oral iron can also be used if the women has severe iron deficiency in the third trimester. Keywords: Intravenous iron delivery routes and anemic pregnant women.